Seasonal drought shapes the relationship between stem CO2 efflux and belowground respiration in an even-age rubber plantation on Hainan Island, China - Xinwei Guo; Bo Song; Rui Sun; Rui Sun; Guoyu Lan; Guoyu Lan; Bangqian Chen; Bangqian Chen; Chuan Yang; Chuan Yang; Zhixiang Wu; Zhixiang Wu (Frontiers in Plant Science, 2025)
IntroductionStem CO2 efflux (Ec) reflects the amount of photo-assimilated carbon released back into the atmosphere and plays a critical role in the carbon balance of tree and forest ecosystems. Despite previous studies indicating that a portion of stem CO2 originates from root respiration (Rroot), the seasonal dynamics of Ec and its relationship with belowground respiration remain poorly understood, particularly in tropical regions characterized by distinct dry and wet seasons.MethodsTo address this gap, we investigated Ec in tapping and non-tapped rubber trees, along with environmental factors and physiological traits (sap flow flux density, root respiration, and leaf area index) from 2018 to 2021.ResultsOur results showed that tapping activity increased the Ec of rubber trees compared to non-tapped trees, with increases ranging from 10.37% to 233.66%. However, the magnitude of this increase varied between the dry and wet seasons. Although tapping enhanced the Ec, it did not alter the Ec seasonal pattern. Consequently, Ec in both tapped and non-tapped rubber trees displayed an overall single-peak pattern, with significantly lower values during the dry season compared to the wet season, suggesting growth phenology primarily regulates Ec seasonal dynamics. Structural equation modeling revealed that root respiration (Rroot), sap flow flux density (Fd), and soil moisture at 50 cm depth as the primary drivers of the Ec variations during the dry season. In contrast, soil moisture at 5 cm depth and air temperature (Ta) were identified as dominant factors influencing Ec in the wet season, with belowground respiration having a negligible influence.DiscussionThese results suggest that the relationship between Ec and belowground respiration is environmentally sensitive and exhibits seasonal dependency.